Counseling children - Thompson, Charles L. (Thomson/Brooks/Cole, 2007)
Unparalleled in its translation of theory into practice, COUNSELING CHILDREN covers the most practical and up-to-date methods for developing effective approaches to counseling children. The authors provide a comprehensive yet easy-to-read text that includes useful strategies and case studies from actual counseling sessions to present a realistic look at the field. COUNSELING CHILDREN presents a development approach to counseling that considers age and stage differences in counseling children, adolescents, and adults